Hsp47: a molecular chaperone that interacts with and stabilizes correctly-folded procollagen - Tasab, Mohammed (Oxford University Press, 2000)
Hsp47 is a heat-shock protein that interacts transiently with procollagen during its folding, assembly and transport from the endoplasmic reticulum (ER) of mammalian cells. It has been suggested to carry out a diverse range of functions, such as acting as a molecular chaperone facilitating the folding and assembly of procollagen molecules, retaining unfolded molecules within the ER, and assisting the transport of correctly folded molecules from the ER to the Golgi apparatus. Here we define the substrate recognition of Hsp47, demonstrating that it interacts preferentially with triple-helical procollagen molecules. The association of Hsp47 with procollagen coincides with the formation of a collagen triple helix. This demonstrates that Hsp47’s role in procollagen folding and assembly is distinct from that of prolyl 4-hydroxylase. These results indicate that Hsp47 acts as a novel molecular chaperone, potentially stabilizing the correctly folded collagen helix from heat denaturation before its transport from the ER.